The status of temporomandibular and cervical spine education in post-professional physical therapy training programs recognized by Member Organizations of IFOMPT: an investigation of didactic and clinical education. (15th March 2018) - Shaffer, Stephen M.; Stuhr, Sarah H.; Sizer, Phillip S.; Courtney, Carol A.; Brismée, Jean-Michel
Abstract: Objectives: The purpose of this investigation was to establish an international baseline of the quantity of physical therapist education on temporomandibular disorders (TMD) during post-professional Orthopedic Manual Physical Therapy (OMPT) education. Methods: An electronically distributed survey was sent to programs and data analyzed for trends, including a comparison of TMD and cervical spine disorders education. Current data were compared to pre-existing data from the United States. Results: For the current data-set, the Mann-Whitney U test demonstrated statistical significance when comparing TMD and cervical spine disorders education for both the hours of didactic training provided ( p < 0.0001) and the number of patients seen during clinical training ( p < 0.006). When comparing the United States and international data, statistically significant greater exposure was reported for both didactic ( p < 0.0001) and clinical education ( p < 0.006) of TMD topics in the United States but not for didactic ( p = 0.23) or clinical education ( p = 0.15) of cervical spine topics. Discussion: These data again indicate a lack of uniformity between post-professional training programs in OMPT with respect to TMD education. There is, however, consistency in that most programs provided more training on cervical spine disorders than TMD. Based on these findings, further investigations are appropriate to determine if TMD education is adequate during post-professional OMPT education.